Role of Mitochondria in Neurodegenerative Diseases: From an Epigenetic Perspective - Xu, Sutong; Zhang, Xi; Liu, Chenming; Liu, Qiulu; Chai, Huazhen; Luo, Yuping; Li, Siguang (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria, the centers of energy metabolism, have been shown to participate in epigenetic regulation of neurodegenerative diseases. Epigenetic modification of nuclear genes encoding mitochondrial proteins has an impact on mitochondria homeostasis, including mitochondrial biogenesis, and quality, which plays role in the pathogenesis of neurodegenerative diseases like Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, and amyotrophic lateral sclerosis. On the other hand, intermediate metabolites regulated by mitochondria such as acetyl-CoA and NAD+, in turn, may regulate nuclear epigenome as the substrate for acetylation and a cofactor of deacetylation, respectively. Thus, mitochondria are involved in epigenetic regulation through bidirectional communication between mitochondria and nuclear, which may provide a new strategy for neurodegenerative diseases treatment. In addition, emerging evidence has suggested that the abnormal modification of mitochondria DNA contributes to disease development through mitochondria dysfunction. In this review, we provide an overview of how mitochondria are involved in epigenetic regulation and discuss the mechanisms of mitochondria in regulation of neurodegenerative diseases from epigenetic perspective.